Modèle flexionnel des unités polylexicales nominales de la langue polonaise - Hajok, Alicja (Neophilologica, 2017)
Traditional dictionaries and electronic dictionaries do not contain necessary information enabling automatic processing of idiomatic expressions. Many a time, an entry, even in a monolexical form, must be representative for the idiom (M e j r i, 2008). Our aim is to create a dictionary of compound nouns customized for the natural language processing. In the following paper we are considering the ways of creating a dictionary of Polish compound nouns. We first describe morpho-syntactic properties of compound nouns, then we propose a morphological analyzer for Polish which enables declination of (i) indeclinable compound nouns ( jo-jo, lelum polelum), (ii) declinable compound nouns (ślepa uliczka, chude lata), (iii) compound nouns containing a declinable and indeclinable elements (herod-baba, języczek u wagi, kraina mlekiem i miodem płynąca).